Untying the Gordian knot of plastid phylogenomic conflict: A case from ferns - Wang, Ting; Li, Ting-Zhang; Chen, Si-Si; Yang, Tuo; Shu, Jiang-Ping; Mu, Yu-Nong; Wang, Kang-Lin; Chen, Jian-Bing; Xiang, Jian-Ying; Yan, Yue-Hong (Frontiers in Plant Science, 2022)
Phylogenomic studies based on plastid genome have resolved recalcitrant relationships among various plants, yet the phylogeny of Dennstaedtiaceae at the level of family and genera remains unresolved due to conflicting plastid genes, limited molecular data and incomplete taxon sampling of previous studies. The present study generated 30 new plastid genomes of Dennstaedtiaceae (9 genera, 29 species), which were combined with 42 publicly available plastid genomes (including 24 families, 27 genera, 42 species) to explore the evolution of Dennstaedtiaceae. In order to minimize the impact of systematic errors on the resolution of phylogenetic inference, we applied six strategies to generate 30 datasets based on CDS, intergenic spacers, and whole plastome, and two tree inference methods (maximum-likelihood, ML; and multispecies coalescent, MSC) to comprehensively analyze the plastome-scale data. Besides, the phylogenetic signal among all loci was quantified for controversial nodes using ML framework, and different topologies hypotheses among all datasets were tested. The species trees based on different datasets and methods revealed obvious conflicts at the base of the polypody ferns. The topology of the “CDS-codon-align-rm3” (CDS with the removal of the third codon) matrix was selected as the primary reference or summary tree. The final phylogenetic tree supported Dennstaedtiaceae as the sister group to eupolypods, and Dennstaedtioideae was divided into four clades with full support. This robust reconstructed phylogenetic backbone establishes a framework for future studies on Dennstaedtiaceae classification, evolution and diversification. The present study suggests considering plastid phylogenomic conflict when using plastid genomes. From our results, reducing saturated genes or sites can effectively mitigate tree conflicts for distantly related taxa. Moreover, phylogenetic trees based on amino acid sequences can be used as a comparison to verify the confidence of nucleotide-based trees.